IValidate: a communication-based clinical intervention in life-limiting illness. Issue Volume 12:Issue e4(2022) (11th April 2019) - Simpson, Nicholas; Milnes, Sharyn; Martin, Peter; Phillips, Anita; Silverman, Jonathan; Keely, Gerry; Forrester, Mike; Dunning, Trisha; Corke, Charles; Orford, Neil
Abstract : Objectives: Report the implementation, user evaluation and key outcome measures of an educational intervention—the iValidate educational programme—designed to improve engagement in shared decision-making by health professionals caring for patients with life-limiting illness (LLI). Design: Prospective, descriptive, cohort study. Participants: Health professionals working in acute care settings caring for patients with an LLI. Main outcomes measured: Participant evaluation of learning outcomes for communication skills and shared decision-making; demographic data of participants attending education workshops; and documentation of patients with LLI goals of management, including patient values and care decision based on area in acute care and seniority of doctor. Results: The programme was well accepted by participants. Participant evaluations demonstrated self-reported improved confidence in the areas of patient identification, information gathering to ascertain patient values and shared decision-making. There was strong agreement with the course-enhanced knowledge of core communication skills and advanced skills such as discussing mismatched agendas. Conclusions: We described the educational pedagogy, implementation and key outcome measures of the iValidate education programme, an intervention designed to improve person-centred care for patients with an LLI. A targeted education programme could produce cultural and institutional change for vulnerable populations within a healthcare institution. A concurrent research programme suggests effectiveness within the current service and the potential for transferability.